Implementasi PPh Pasal 22 atas Investasi Emas Berdasarkan PMK Nomor 48 Tahun 2023 - Jenie Jesicca Hr; Ratna Septiyanti (GLOBAL SCIENTS PUBLISHER, 2026)
This research focuses on examining how Article 22 Income Tax is applied to gold investment transactions in light of the Minister of Finance Regulation Number 48 of 2023, as well as its effects on the public's interest in gold investments. The study utilizes a descriptive qualitative approach, relying on secondary data gathered through documentation and literature analysis. The findings show that the application of Article 22 Income Tax has been implemented through a unified system, in which tax collection is managed by gold producers, and the tax is directly added to the price for consumers. The decrease in tax rates from 0. 45% to 0. 25% considerably reduces the tax burden, allowing gold prices to be more competitive. Moreover, this initiative aids in creating a more streamlined gold spread, thus enhancing the appeal of gold investments for the general public. As a result, this tax initiative not only improves the efficiency of tax collection but also contributes to the growth of investments and stimulates economic activity within the gold trading industry.